2001
DOI: 10.1073/pnas.191124098
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the human CD4 N-terminal two-domain fragment complexed to a class II MHC molecule

Abstract: The structural basis of the interaction between the CD4 coreceptor and a class II major histocompatibility complex (MHC) is described. The crystal structure of a complex containing the human CD4 N-terminal two-domain fragment and the murine I-A k class II MHC molecule with associated peptide (pMHCII) shows that only the ''top corner'' of the CD4 molecule directly contacts pMHCII. The CD4 Phe-43 side chain extends into a hydrophobic concavity formed by MHC residues from both ␣2 and ␤2 domains. A ternary model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
200
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(205 citation statements)
references
References 49 publications
5
200
0
Order By: Relevance
“…However, it is noteworthy that several Ig superfamily receptors engage viral ligands via the GFCCЈ ␤-sheet. The HIV glycoprotein gp120 binds to residues on the GFCCЈ face of its receptor CD4 (47), and the same region of CD4 also interacts with its natural ligand MHC class II (48). Complexes of rhinoviruses and coxsackievirus A21 with their receptor intercellular adhesion molecule-1 (ICAM-1) also show that the interactions involve residues at the top of ICAM-1 D1, a region that includes part of the GFCCЈ face (49,50).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is noteworthy that several Ig superfamily receptors engage viral ligands via the GFCCЈ ␤-sheet. The HIV glycoprotein gp120 binds to residues on the GFCCЈ face of its receptor CD4 (47), and the same region of CD4 also interacts with its natural ligand MHC class II (48). Complexes of rhinoviruses and coxsackievirus A21 with their receptor intercellular adhesion molecule-1 (ICAM-1) also show that the interactions involve residues at the top of ICAM-1 D1, a region that includes part of the GFCCЈ face (49,50).…”
Section: Resultsmentioning
confidence: 99%
“…CD4 dimerization could not be observed in the cocrystal of CD4 with MHC class II, since the CD4 component included only the two N-terminal domains of CD4. Arguing against CD4 dimerization, this recent study has reported that alanine substitutions of residues K318 and Q344 are without effect on CD4-MHC II binding, measured by rosette formation between CD4-transfected COS-7 cells and MHC II-expressing Raji cells (42). There are several possible explanations for these findings: 1) overexpression of CD4 molecules in COS-7 cells might facilitate cell-cell adhesion and thus bypass the need for CD4 dimerization in rosette formation; and 2) CD4 dimerization might be required only for T cell activation, when the TCR recognizes its nominal Ag on the MHC.…”
Section: Discussionmentioning
confidence: 99%
“…The role of CD4 in stimulation by heterodimers was also tested in these studies. The original pseudodimer model was partly based on structural data from Reinherz and colleagues 18 , showing that CD4 binds to MHC class II at an angle that would not allow a CD4 molecule to bind the same MHC molecule that the TCR is engaging (Fig.4). Supporting this model are also earlier studies showing that a large fraction of TCRs are constitutively associated with CD4 molecules on antigen experienced T cells.…”
Section: Contribution Of Endogenous Peptides In Cd4 + T-cell Activationmentioning
confidence: 99%